Ståndortsanpassning och produktionspotential för björk i Gävleborgs län - Gustafsson, Sven; Rudhe, Jacob (SLU/Dept. of Forest Ecology and Management, 2012)
Large amounts of birch-timber are imported to Sweden, from particularly the Baltic States, since the domestic production can’t support the pulp industry. The goal of this study was to show the potential of birch and the area’s most suitable for birch production. The study was limited to Gävleborg County.